2023
DOI: 10.1109/access.2023.3254503
|View full text |Cite
|
Sign up to set email alerts
|

1000 Days of COVID-19: A Gender-Based Long-Term Investigation into Attitudes With Regards to Vaccination

Abstract: The coronavirus pandemic has undoubtedly been one of the major recent events that have affected our society at the global level. During this period, unprecedented measures have been imposed worldwide by authorities in an effort to contain the spread of the disease. These measures have led to a worldwide debate among the public, occurring not least within the forum of social media, tapping into preexisting trends of skepticism, such as vaccine hesitancy. At the same time, it has become apparent that the pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…These pre-processing actions are needed, as it has been proven that they are crucial in achieving results that are as close as possible to the users' opinions [3]. To this extent, the ekphrasis library, the Natural Language Toolkit (NLTK) library, and the "re" Python module are used [36,[56][57][58]. Next, the text is represented as numbers to ensure that it can be handled by the The results in terms of annotation are compared between the three annotators, and, in the case of disagreement, the category mentioned by most of the annotators is selected.…”
Section: Dataset Collectionmentioning
confidence: 99%
“…These pre-processing actions are needed, as it has been proven that they are crucial in achieving results that are as close as possible to the users' opinions [3]. To this extent, the ekphrasis library, the Natural Language Toolkit (NLTK) library, and the "re" Python module are used [36,[56][57][58]. Next, the text is represented as numbers to ensure that it can be handled by the The results in terms of annotation are compared between the three annotators, and, in the case of disagreement, the category mentioned by most of the annotators is selected.…”
Section: Dataset Collectionmentioning
confidence: 99%
“…They found that their framework offers some key advantages: first, the method creates clusters without requiring users to label; second, they do not require domain-or topic-level knowledge to conduct the labeling. Kovacs, Cotfas, Delcea, and Florescu (2023) analyze the tweets about COVID-19 vaccination using the SVM model to identify the gender of the author, the result showed 85% classification accuracy. Also, they detected the stance and showed that RoBERTa was the most effective classifier accuracy 93.64%.…”
Section: Related Workmentioning
confidence: 99%
“…People used different social media platforms to express their worries about their safety and report vaccines' side effects they experienced [15]. Analyzing the opinion from vaccinated people could give more insight around the vaccines [16], [17] and their side effects rather than depending only on clinical studies and reports.…”
Section: Introductionmentioning
confidence: 99%